2019
DOI: 10.1158/1078-0432.ccr-19-1133
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and Safety of Rovalpituzumab Tesirine in Third-Line and Beyond Patients with DLL3-Expressing, Relapsed/Refractory Small-Cell Lung Cancer: Results From the Phase II TRINITY Study

Abstract: Purpose: Although extensive-stage small-cell lung cancer (SCLC) is highly responsive to first-line therapy, virtually all patients develop resistance with short survival. Rovalpituzumab tesirine (Rova-T) is an antibody-drug conjugate targeting delta-like 3 protein (DLL3). This open-label, single-arm, phase II study (TRINITY) assessed safety and efficacy of Rova-T in patients with DLL3-expressing SCLC in the third-line and beyond (3Lþ) setting. Patients and Methods: Patients with DLL3-expressing SCLC (determine… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
179
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 223 publications
(187 citation statements)
references
References 33 publications
7
179
1
Order By: Relevance
“…A primary criterion for efficient drug delivery is to choose an exclusively or overexpressed target for the cancer cells. Figures 6I and S6 show the expression of two receptors of clinical ADCs in the SCLC cell lines: DLL3 (used for SCLCs as rovalpituzumab tesirine [Rova-T]; Morgensztern et al, 2019 ; Rudin et al, 2017 ) and the carcinoembryonic antigen CEACAMC5 (used in other clinical indications as labetuzumab govitecan; Das, 2017 ). DLL3 expression is highly correlated with ASCL1 expression (p = 0.62), suggesting that targeting DLL3 could be selective toward SCLC-A tumors.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…A primary criterion for efficient drug delivery is to choose an exclusively or overexpressed target for the cancer cells. Figures 6I and S6 show the expression of two receptors of clinical ADCs in the SCLC cell lines: DLL3 (used for SCLCs as rovalpituzumab tesirine [Rova-T]; Morgensztern et al, 2019 ; Rudin et al, 2017 ) and the carcinoembryonic antigen CEACAMC5 (used in other clinical indications as labetuzumab govitecan; Das, 2017 ). DLL3 expression is highly correlated with ASCL1 expression (p = 0.62), suggesting that targeting DLL3 could be selective toward SCLC-A tumors.…”
Section: Resultsmentioning
confidence: 99%
“…Second, we highlight potential surface markers that could be targeted on the basis of the NAPY subgroups. For example, SCLC-Y cells express neither the therapeutically relevant surface epitopes DLL3 or CEACAM5 ( Das, 2017 ; Morgensztern et al, 2019 ; Rudin et al, 2017 ), which tend to be specific for the SCLC-A (and N). However, SCLC-Y express CD151 and EPHA2 ( Figure 6K ) and might respond to the YAP1 and NOTCH inhibitors in clinical development ( Crawford et al, 2018 ; Leonetti et al, 2019 ).…”
Section: Discussionmentioning
confidence: 99%
“…After this trial, phase 2 clinical trial assessed safety and efficacy of Rova-T for patients with DLL3 expression-positive SCLC in the third-line and beyond setting (TRINITY), and the results demonstrated modest clinical activity with associated toxicities. 27 The anti-DLL3/CD3 Bispecific T cell engager (BiTE) antibody (AMG 757) and a chimeric antigen receptor T cell therapy targeting DLL3 (AMG119) have been clinically evaluated in phase 1 clinical trials for the treatment of relapsed/refractory SCLC. 28 There is increasing evidence that surgical resection alone is insufficient for treating LCNEC, 3 and several researchers have reported that adjuvant platinum-based chemotherapy for patients with LCNEC dramatically improved the surgical outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…Median OS was 5.6 months in all patients. 104 On August 29,2019 AbbVie announced that the Phase 3 MERU study (NCT03033511), which was evaluating rovalpituzumab tesirine as a first-line maintenance therapy for advanced small cell lung cancer, demonstrated no survival benefit at a preplanned interim analysis for patients receiving the drug as compared with placebo. The MERU trial is being closed, and the research and development program for rovalpituzumab tesirine has been terminated.…”
Section: Rovalpituzumab Tesirine (Abbvie Inc)mentioning
confidence: 99%